Sistem Aplikasi Pengecekan Kerusakan Pada Kendaraan - Sofyan Mufti Prasetiyo; Ade Dewa; Alvinda Shahrul; Husain Lutfi (CV. Multi Kreasi Media, 2023)
The development of technology in this era as well as development in the detection of a damage to a car from a symptom that arises is the cause of car damage, namely the application of an expert system, which in this application explains several types of damage, starting from the characteristics of damage symptoms, types of damage and solutions to damage that occurs in vehicles. most vehicle owners still don't understand the damage that often occurs to their vehicle components.With this system, the author tries to design an expert system that can assist vehicle owners in overcoming problems that often arise in vehicles so that owners can find out what they need repaired, checking during emergencies, and often having problems with vehicles. In designing this program can explain that a a system that runs with an algorithm design and knowledge base including expert tables and a decision tree of a program so that with this the program can know what are the deficiencies and specifications needed in this system. To complete, there is data collection using a questionnaire to determine the level of feasibility and maturity of this system according to what you expect, then proceed with analyzing these processes.